2020
DOI: 10.1177/0268355519898320
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the positional relationship between the left brachiocephalic vein and its surrounding vessels via computed tomography scan: A retrospective study

Abstract: Objectives This study aimed to clarify the positional relationship between the left brachiocephalic vein and its surrounding vessels and to analyse the association between this positional relationship and ageing. Method Chest contrast-enhanced computed tomography was performed for 100 adults. The contact number between left brachiocephalic vein and surrounding vessels (aorta, brachiocephalic artery, left common carotid artery and left subclavian artery) was determined. The correlations of ageing with the cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…In the data evaluated as part of the present study, the phenomenon of LBCV compression was observed in patients of advanced age, with severe LBCV compression detected at the sites of the vessel's contact with the BCT and/or left CCA. A retrospective analysis of 100 CT images by Mitsuoka et al demonstrated analogous locations of the points of direct contact between the LBCV and the adjacent arteries (the BCT in 97 cases, the left CCA in 90 cases, and the left SA several times less commonly) [3].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…In the data evaluated as part of the present study, the phenomenon of LBCV compression was observed in patients of advanced age, with severe LBCV compression detected at the sites of the vessel's contact with the BCT and/or left CCA. A retrospective analysis of 100 CT images by Mitsuoka et al demonstrated analogous locations of the points of direct contact between the LBCV and the adjacent arteries (the BCT in 97 cases, the left CCA in 90 cases, and the left SA several times less commonly) [3].…”
Section: Discussionmentioning
confidence: 96%
“…A favourable spatial relationship of the LBCV with the sternum and with the aortic arch [or its branches: the brachiocephalic trunk (BCT), left common carotid artery (CCA), and left subclavian artery (SA)] facilitates uneventful CIED or CVC placement [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…The most typical left BCV topography involves the vein coursing above the aortic arch (AA) and anterior to its branches (the brachiocephalic trunk, left common carotid artery, and left subclavian artery. Once it crosses to the right side of the upper mediastinum, the left BCV joins the right BCV to form the SVC [4].…”
Section: Discussionmentioning
confidence: 99%
“…Performing minimally invasive transvenous procedures, such as cardiac implantable electronic device (CIED) implantation, facilitates making observations as to the individual differences in vessel layout. These differences can be due to either normal anatomical variations or developmental anomalies [1,2,3,4].…”
Section: Introductionmentioning
confidence: 99%